LAWS AND OBSTACLES IN COUNTERING TERRORISM AND HUMAN RIGHTS VIOLATIONS - Archi Rafferti Kriswandanu (Universitas 17 Agustus 1945 Semarang, 2022)
Terrorism is an extraordinary crime that is of concern to the world today. Not just acts of terror alone, but acts of terrorism also violate human rights as fundamental rights that are naturally inherent in human beings, namely the right to feel comfortable and safe or the right to live. In addition, terrorism also causes casualties and damage to property. Acts of terrorism also damage the country’s stability, especially in the economy, defense, security, etc. Meanwhile, sociologically, acts of terrorism damage spiritual values in the order of social life by giving rise to religious arguments as justification for these acts of terror. The impact of this crime is innocent people who are victims of heinous and inhuman acts of terrorism. This is what underlies the importance of solving the problem of terrorism completely.